Challenging Disease Ontology by Instances of Atypical PKHD1 and PKD1 Genetics - de Fallois, Jonathan; Schönauer, Ria; Münch, Johannes; Nagel, Mato; Popp, Bernt; Halbritter, Jan (Frontiers in Genetics, 2021)
Background Autosomal polycystic kidney disease is distinguished into dominant (ADPKD) and recessive (ARPKD) inheritance usually caused by either monoallelic (PKD1/PKD2) or biallelic (PKHD1) germline variation. Clinical presentations are genotype-dependent ranging from fetal demise to mild chronic kidney disease (CKD) in adults. Additionally, exemptions from dominant and recessive inheritance have been reported in both disorders resulting in respective phenocopies. Here, we comparatively report three young adults with microcystic-hyperechogenic kidney morphology based on unexpected genetic alterations beyond typical inheritance. Methods Next-generation sequencing (NGS)-based gene panel analysis and multiplex ligation-dependent probe amplification (MLPA) of PKD-associated genes, familial segregation analysis, and reverse phenotyping. Results Three unrelated individuals presented in late adolescence for differential diagnosis of incidental microcystic-hyperechogenic kidneys with preserved kidney and liver function. Upon genetic analysis, we identified a homozygous hypomorphic PKHD1 missense variant causing pseudodominant inheritance in a family, a large monoallelic PKDH1-deletion with atypical transmission, and biallelic PKD1 missense hypomorphs with recessive inheritance. Conclusion By this report, we illustrate clinical presentations associated with atypical PKD-gene alterations beyond traditional modes of inheritance. Large monoallelic PKHD1-alterations as well as biallelic hypomorphs of both PKD1 and PKHD1 may lead to mild CKD in the absence of prominent macrocyst formation and functional liver impairment. The long-term renal prognosis throughout life, however, remains undetermined. Increased detection of atypical inheritance challenges our current thinking of disease ontology not only in PKD but also in Mendelian disorders in general.